2012
DOI: 10.1097/fpc.0b013e32835693f7
|View full text |Cite
|
Sign up to set email alerts
|

Association of COMT, MTHFR, and SLC19A1(RFC-1) polymorphisms with homocysteine blood levels and cognitive impairment in Parkinson’s disease

Abstract: The genetic factors studied were not associated with cognitive status in PD patients. Only age and Hcy plasma levels were found to be independent risk factors predisposing individuals to PD dementia. However, COMT: rs4680: A>G and rs4633: C>T polymorphisms were found to significantly affect PD risk, and the MTHFR 677C>T polymorphism helped determine plasma Hcy concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 50 publications
3
49
2
Order By: Relevance
“…In contrast, the Honolulu-Asia Aging Study cohort and case-control studies from three regions in China (N > 6,000) found no relationship between folate or vitamin B 12 intake or status and risk for Parkinson's disease (53,113,114). However, a recent meta-analysis of 14 studies found that elevated plasma Hcy was an independent risk factor for Parkinson's disease (96,115,116).…”
Section: Folatementioning
confidence: 93%
See 2 more Smart Citations
“…In contrast, the Honolulu-Asia Aging Study cohort and case-control studies from three regions in China (N > 6,000) found no relationship between folate or vitamin B 12 intake or status and risk for Parkinson's disease (53,113,114). However, a recent meta-analysis of 14 studies found that elevated plasma Hcy was an independent risk factor for Parkinson's disease (96,115,116).…”
Section: Folatementioning
confidence: 93%
“…Hyperhomocysteinemia is related to cognitive impairment in Parkinson's disease patients (115). Lower folate and vitamin B 12 levels and higher Hcy levels were found in a meta-analysis of 15 studies of Parkinson's disease patients with cognitive dysfunction (115). Further, as Parkinson's disease progressed levels of vitamin B 12 decreased, and low B 12 was associated with greater disease severity (113,116).…”
Section: Vitamin B 12mentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent study performed in Indian subjects failed to find association of the RFC-1 80G>A polymorphism with risk of AD or vascular dementia, and no association of the polymorphism with serum folate levels was detected [21]. Moreover, others failed to observe association of rs1051266 with cognitive status, folate, and hcy levels in Caucasian Parkinson's disease (PD) patients [22]. …”
Section: Introductionmentioning
confidence: 99%
“…It has been well established that elevated serum homocysteine level, namely, hyperhomocysteinemia (hHcys), is associated with a wide range of diseases and pathologic processes, including neurologic (Ravaglia et al, 2005;Białecka et al, 2012;Perła-Kaján and Jakubowski, 2012), cardiovascular (Cavalca et al, 2001;Białecka et al, 2012) and kidney (Wu et al, 2012) disease, osteoporosis (McLean et al, 2004), and complications of aging (Yu et al, 2012). With respect to glomerulosclerosis and consequent end-stage renal disease (ESRD), a large body of evidence supports a pathogenic role of hHcys via its effects on extracellular matrix accumulation, mesangial expansion, podocyte injury, local oxidative stress, and inflammation (Yi et al, 2007;Zhang et al, 2010;Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%